Normocentrism, diversity, and otherness: Deconstructing Chilean inclusive education policies - Hugo Parra Munoz; Catalina Garrido Reyes; Andrea Carrasco Lobos; Mauricio Vergara Rodríguez; Felipe Hidalgo Kawada; David Meza Buzzetti (Arizona State University, 2020)
During recent decades, and in the context of global movements for educational reforms, a series of inclusive policies have been enacted in Chile. Based on these transformations, the objective of this article is to analyse a set of policies aimed at the attention of special needs students. Methodologically, a documentary work was conducted, in which texts related exclusively to the attention of students with special needs were selected, and which were temporarily published between 1990 and 2018. Thus, a corpus of 14 documents was obtained, seven of which are analysed in-depth in this article. The analysis of the texts occurred in two phases: first, from a hermeneutical distancing process (Ricoeur, 1986, 2003), and, later, from a deconstructive analysis (Derrida, 1997). Among the most relevant findings, the binarisation of inclusion is observed, reducing it to the erection of barriers of accessing and teaching, and the shifting from disciplinary logic associated to normalisation to others of self-regulation. Finally, the emergence of logics of standardised difference was observed, which leans toward a normocentrality, where otherness would be understood as threat.